A short survey on oral poetry as ritual performance. The sicilian Cunto as case study (Mantichora. Italian Journal of Performance Studies, 2020)
This paper aims to investigate the performative nature of oral poetry. In particular, we intend to focus on peculiar Sicilian phenomenon called Cunto which throughout a knowing mixing of rhyme and breath provides the storytelling with a tremendous and unique impact.